Cononic analysis of the relationship between test anxiety and motivation to progress with self-disability and academic procrastination in students of Tehran University of Applied Sciences - Leyla Shamsnezhad; Davoud Hosseini Nasab; Sholeh Livarjani (پژوهش در نظام‌های آموزشی, 2020)
The aim of this study was to investigate the relationship between test anxiety and motivation to progress with self-disability and academic procrastination in students of Tehran University of Applied Sciences. The research method of the present study is descriptive-correlational. The statistical population of this study includes all students of East Tehran University of Applied Sciences. 340 people were selected from this statistical population by multi-stage random sampling method. The negligence of Solomon and Rothblum (2005) and Edward E. Jones's (1979) self-restraint scale were answered. The results of Pearson correlation showed that there is a positive and significant relationship between test anxiety and academic self-efficacy and there is a negative and significant relationship between achievement motivation and self-efficacy and academic achievement. Negativity and test anxiety positively predict students' procrastination and self-empowerment. The results of the study indicate that by increasing the motivation to progress and reduce the anxiety of the exam, it is possible to reduce the students' self-disability and academic procrastination.